2011
DOI: 10.5194/acp-11-2015-2011
|View full text |Cite
|
Sign up to set email alerts
|

VOCALS-CUpEx: the Chilean Upwelling Experiment

Abstract: Abstract. The VAMOS Ocean-Cloud-Atmosphere-Land Study Regional Experiment (VOCALS-REx) was a major field experiment conducted in spring of 2008 off southern Peru and northern Chile, aimed at better understanding the coupled climate systems of the southeast Pacific. Because of logistical constrains, the coastal area around 30 • S was not sampled during VOCALS-REx. This area not only marks the poleward edge of the subtropical stratocumulus cloud regime (thus acting as a source of transient disturbances) but is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 37 publications
4
33
0
Order By: Relevance
“…Despite the small differences in SST regimes detected, these confirm the difference in mesoscale oceanographic conditions across PLV. Our results are in good agreement with previous work showing significant differences between north and south PLV in terms of SST, CO 2 saturation, and the magnitude and variability of wind speed [22], [32], [66], which can be associated with temporal fluctuations in primary productivity [36]. Accordingly, the spatiotemporal variation in SST is well correlated with that in biological oceanographic features and supports our interpretation of SST patterns as a proxy for local environmental conditions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the small differences in SST regimes detected, these confirm the difference in mesoscale oceanographic conditions across PLV. Our results are in good agreement with previous work showing significant differences between north and south PLV in terms of SST, CO 2 saturation, and the magnitude and variability of wind speed [22], [32], [66], which can be associated with temporal fluctuations in primary productivity [36]. Accordingly, the spatiotemporal variation in SST is well correlated with that in biological oceanographic features and supports our interpretation of SST patterns as a proxy for local environmental conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, events of relaxation from upwelling are more frequent south than north of PLV [29]. Episodes of sea surface warming after relaxation from upwelling dominate high-frequency variability in SST, particularly during spring [32]. Such warm events can play a key biological role as onshore advection of recently upwelled waters can bring planktonic larvae and high nutrient concentrations to the intertidal community [35] and can lead to phytoplankton blooms nearshore [36].…”
Section: Methodsmentioning
confidence: 99%
“…The data collected by the R/V Olaya reveal a great deal of alongshore variability of the near-surface wind field with local maxima just to the north of major headlands and minima farther downstream (e.g., Rahn et al 2011). Along the coast for more than 700 km between Arica (18°S) and Paposo (25°S), the seasonal mean height of the MBL inversion is remarkably uniform at about 1000 m above mean sea level, which is the approximate elevation of the coastal range, although SST cools gradually from north to south (Rahn and Garreaud 2010a).…”
Section: The Coastal Circulationmentioning
confidence: 99%
“…In a previous modeling study, Capet et al (2004) suggested that a poor representation of the wind drop-off off the coast of California could underestimate Ekman pumping and overestimate coastal upwelling (and vice versa), with consequences for the coastal circulation processes. Meanwhile, Garreaud et al (2011), using observations, found a local atmospheric coastal jet just north of one of the most prominent geographic points of the region: Punta Lengua de Vaca (see Fig. 1).…”
mentioning
confidence: 99%